Information, Polarization and Delegation in Democracy - Christian Schultz (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper investigates the merits of different democratic institutions when politics is uni-dimensional, there is uncertainty both about the preferences of the future electorate and the future polarization of political parties, and politicians have better information about the state of the world than voters. Three types of institutions are compared: direct democracy, representative democracy where politicians are accountable, and independent agencies where they are not. Low uncertainty about the state of the world and the future electorates preferences and high expected polarization make direct democracy optimal, while the opposite configuration makes representative democracy optimal. Independent agencies are optimal for intermediate values.
Keywords: H1; H7; K4; 330; accountability; redistribution; constitutional design; voting; information; direct democracy; Demokratie; Wahl; Information; Verfassungsreform